2019
DOI: 10.1016/j.apenergy.2018.10.097
|View full text |Cite
|
Sign up to set email alerts
|

City-level water-energy nexus in Beijing-Tianjin-Hebei region

Abstract: Water-energy nexus in a city can either prompt or undermine its development. Yet in China, the relevant research is rarely found. This study accounts the city-level water-energy nexus in Beijing-Tianjin-Hebei region in 2012 from both production and consumption perspectives, where input-output analysis based on city-level input-output tables are applied to conduct consumption-based accounts. Regarding water for energy, Beijing, Tianjin and Tangshan occupy the largest amounts of water for production in the energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 54 publications
1
40
0
1
Order By: Relevance
“…Some cities, such as Hengshui, Yantai, and Qingdao, have less water withdrawal per capita and lower water withdrawal intensity than others. Apart from a less water-consumptive production structure (Li et al, 2019b), some other possible reasons for this difference could be that these areas have advanced water conservation technology.…”
Section: Applications Of the Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Some cities, such as Hengshui, Yantai, and Qingdao, have less water withdrawal per capita and lower water withdrawal intensity than others. Apart from a less water-consumptive production structure (Li et al, 2019b), some other possible reasons for this difference could be that these areas have advanced water conservation technology.…”
Section: Applications Of the Methodologymentioning
confidence: 99%
“…We ranked the water withdrawals of the secondary sectors in each city and identified the top three water users for each city, as indicated by the numbers and squares in For the industrial sectors, the high users at the city level include smelting and pressing of ferrous metals and mining and processing of ferrous metal ore, after the production and supply of electricity and hot water and raw chemical materials and products. Water is most used in industrial processes, such as mining, processing, cooling, air conditioning, clarifying, and washing (Fan et al, 2019b(Fan et al, , 2019cLi et al, 2019b). Similarly, the three services with the highest water use at the city level are accommodation and catering, education, and public management, social security.…”
Section: A Comparison Of Top Water-use Sectors At the City Level Aftementioning
confidence: 99%
“…Considering the implement of the recent development plan ("The development of Xiongan New Area" and the "Two-child Policy"), hosting the Winter Olympic Games, and the technological innovation in the energy sector, without a doubt, it will exert great influence on the tense relationship between water and energy in Hebei Province. At this stage, studies focused on Hebei is commonly found on water-energy nexus and the decomposition analysis of water utilization in Jing-Jin-Ji region (Wang et al, 2015;Sun et al, 2018;Li X. et al, 2019). Specifically, for Hebei Province, Lv et al (2018) identified optimal strategies for the energy-water nexus system under multiple uncertainties and various water-saving scenarios (Lv et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The urban agglomeration is also one of the most carbon-intensive regions in China. 30 Interregional coordinated strategies for low carbon development and water supply are the main concerns of local governance. Although many studies have focused on the problems, the scope of these studies to trace the supply chain between Beijing, Tianjin, and Hebei was at the regional level due to the methodology used and the data available at the time.…”
Section: Introductionmentioning
confidence: 99%